Os impactos do Plano Nacional de Políticas para as Mulheres nos serviços de atendimento às mulheres em situação de violência do município de Serra/ES - Ribeiro, Daniella Borges (2008)
The purpose of this study is to analyse the creation and development of services for women subject to violence in the municipality of Serra, using The National Policy Plan for Women as a reference. First of all we conducted a survey of existing services in the municipality and subsequently carried out interviews. This fact finding study consists of information gathered from documents and semi-structured interviews with nine professionals of the six services researched. The interviews were recorded, transcribed and their content analyzed. Of the nine subjects interviewed, five proved to have a deeper knowledge of the National Policy Plan for Women, and six pointed out that they had participated in technical discussions on violence against women. The lack of human and financial resources surfaced as the main problems, and we observed that some of the professionals were unaware of financial recources that should be available to their services. Of the six services researched, two were formed before 2004, with Pró-Vida being the most focused on. The other four services were formed after 2004, and interviewees from these drew particular attention to the court of violence against women. We can verify that some of the professionals are working towards creating a networking system and the setting up of discussions and meetings. On a municipal / state level there were no call centres exclusive to women subject to violence. However, on a federal level the 180 number was created specifically for this purpose. Overall, the National Policy Plan for Women was revealed to be an important instrument in drawing attention to certain policies regarding women, and in carrying out some actions. All things considered, it should not have the sole responsibility of formulating and executing social policies. Pressure and demands on the part of society and especially from social movements, are essential in forcing the state to actively monitor the policies being implemented.